Development of UV-VIS Spectrophotometer Virtual Laboratory Media for Instrumental Analytical Chemistry Digital Practicum - Zurweni Zurweni; Aulia Sanova (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
The demands of 21st Century learning are now in the Industrial Revolution Era 4.0 with 4C learning characters. Educators must develop their creativity to improve the quality of learning so that students can be more creative in learning. Instrumental Analytical Chemistry is a course that studies modern instrumentation for chemical analysis. The instrumentation is unavailable in the laboratory because it is costly. This research aims to develop a virtual laboratory media UV-Vis Spectrophotometer that can be used in the digital practicum of the Instrumental Analytical Chemistry Course. The method used is development research (R & D) by adapting the multimedia model ID Hannafin & Peck, using Macromedia flash applications. This research shows that the UV-Vis Spectrophotometer virtual lab developed provides excellent feasibility results and is also effective for use in lectures and digital practicum of Instrumental Analytical Chemistry lectures.